The Effect and Perdurability of Fatigue of Lower Extremity Muscles on the Time to Stabilization at a Single-Leg Jump Landing in Adult Men Iranian Handball Super League Players - Mehdi Khaleghi-Tazji; Heydar Sadeghi; Naji Ghahremani (Vesnu Publications, 2018)
Introduction: Increase in the time to stabilization (TTS) can lead to injury. Therefore, the assessment of fatigue in context of injury and its relationship with time to stabilization can be useful. The aim of this study was assessment of the effect and perdurability of fatigue of lower extremity muscles on time to stabilization at a single-leg jump landing in adult men Iranian handball super league players. Materials and Methods: Ten male Iranian super league handball players (during the super league year 2014-2015) participated in this study. Three repetitions were considered for the landing leg, and ground reaction forces were recorded for 20 seconds from touching instance force plate. Fatigue of hip, knee, and ankle joint muscles was conducted at 24-hour intervals using isokinetic dynamometer device. Afterwards, the participants carried out jump-landing movement in two session, immediately and 10 minutes after fatigue protocol. Time to stabilization was measured in anterior-posterior and medio-lateral directions. Shapiro-Wilks test was used to assess normality of the data, and repeated measures analysis of variances (ANOVA) and Bonferroni tests were used to evaluate the research hypotheses. Results: The repeated measures ANOVA showed a significant difference in time to stabilization between different conditions (pre, immediate, and 10 minutes after fatigue protocol of invertor and evertor muscles) in anterior-posterior direction (P < 0.001); but there was no significant difference in medio-lateral direction (P = 0.650). There was also a significant difference in time to stabilization of anterior-posterior direction between different conditions (P = 0.003) after fatigue protocol of flexor-extensor knee joint; but there was no significant difference in medio-lateral direction (P = 0.228). Time to stabilization did not show significant difference in both anterior-posterior (P = 0.051) and medio-lateral (P = 0.343) directions after fatigue protocol of abductor-adductor hip muscle. Conclusion: In general, it can be concluded that exhaustive fatigue of lower extremity muscles (ankle, knee, and hip) leads to increase in time to stabilization and the force exerted on the leg, and may contribute to injury. Therefore, by designing and implementing special endurance training programs, it is possible to minimize time to stabilization in jump-landing movements, and eventually reduce risk of injury.